Factores desencadenantes y etiología de hematomas intraparenquimatosos en pacientes hospitalizados en el Área de Neruología Clínica y Neurocirugía del Hospital Isidro Ayora, periodo enero a diciembre del 2011. - Carrión Martínez, Pablo Fernando (2013)
Today intraparenchymal hematomas presented worldwide, is one of the main problems that cause a high degree of both motor and cognitive disabilities that make it a poor prognosis because of its labor problems, economic, social and even the family sphere. Due to this high rate of neurovascular pathology has served me incentive to develop this research topic. That is a retrospective, descriptive and transversal in the months from January to December of 2011, in order to determine TRIGGERS AND ETIOLOGY OF HEMATOMAS intraparenchymal IN INPATIENT IN THE AREA OF CLINICAL NEUROLOGY AND NEUROSURGERY, plus age group , gender . The universe is made of 681 patients admitted to the hospital's neurosurgery department Isidro Ayora de Loja , of which we chose a sample of 138 patients with a diagnosis of intracerebral hematoma , to which investigated through clinical history , factors triggers , etiology, age group and gender . We excluded those patients with no diagnosis of intracerebral hematoma and who are hospitalized in areas other than clinical neurology and neurosurgery at the Hospital Isidro Ayora. Of the 138 patients investigated, in terms of etiology, 42% are hypertension, closely followed head injury with 30%, the age group is the most predominant was between 61-70 years, 56, 5% corresponds to female and 43.5% were male, the most common risk factors are hypertension, tce and diabetes, and alcoholism. KEYWORDS: Intracerebral hematoma, triggers, etiology.